Peaceful heart : the Buddhist practice of patience - Kongtrul, Dzigar (Shambhala, 2020)
"An introductory guide to cultivating patience and opening your heart to difficult circumstances from leading Buddhist teacher, Dzigar Kongtrul Rinpoche. Patience is one of the most important qualities we can develop, as it represents our mind's ability to work positively with anything that bothers us, including anger, loss, jealousy, and helplessness. We are consistently confronted with situations or outcomes we weren't expecting or didn't want, and our default response is to reject what happened with feelings of mild irritation, inward complaining, self-aggression, or seething resentment. Patience is an antidote to all these forms of rejection. Those who have mastered patience have learned to welcome all challenging situations, people, and emotions as opportunities to open their hearts rather than close them. Based on the teachings of the sixth chapter of Shantideva's The Way of the Bodhisattva, Peaceful Heart explores how Buddhist teachings on patience can help you work with whatever disturbances arise in your life and in your mind. Dzigar Kongtrul provides practices and examples throughout the book to challenge readers on the path to developing a more patient heart"--